Pass-through Effect from Exchange Rates to the Prices in the Framework of Inflation Targeting Policy: A Comparison of Asia-Pacific, South American and Turkish Economies - Karagoz, Murat; Demirel, Baki; Bozdag, Emre Guneser (ELSEVIER SCIENCE BV, 2016)
Most of the emerging market economy in 90s faced to grave crisis. After these crises, the monetary policies of emerging market economies gave up to use exchange rates as an anchor. For such markets inflation targeting became a new policy. Exchange rates' overshooting effects in the markets and consequential troubles are important causes of these political changes. The study aims at comparatively measuring the pass through impacts of exchange rates to the prices in Asia Pacific, Latin (South) America, and Turkey economies, which implement inflation targeting regime, but have the variable traits in dollarization and inflation experiences For calculating of pass-through effects from exchange rates to domestic prices, the model that is used in the study has five variable factors. Analysis of model is base of VAR approach. Due to cross section series are used in addition to time series, Panel VAR model has been used. Upon obtained findings, it can be said that pass-through effect in Asia Pacific economies is lower than pass-through effect in Latin America and Turkey. This result also complies with the examined pass-through effect literature.(dagger) (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Inflation Targeting; Pass-Through Effects; Exchange rates; Prices; Business & Economics